Effects of Coarse Aggregate Shape and Texture on Engineering Properties of Roller Compacted Concrete Prepared for High Traffic Routes - Ogbonna Alban Chidiebere (Romanian Journal of Transport Infrastructure, 2021)
Use of roller-compacted concrete in pavement construction is increasing. Roller compacted concrete is a zero-slump, highly compacted concrete that is placed by equipment similar to that used in asphalt pavement construction. This investigation was conducted to collect the state-of-the-art information on effects of coarse aggregate size and texture on the strength and workability of roller-compacted concrete (RCC) for pavement construction and maintenance. Concrete specimens containing cubical and rough coarse aggregate, irregular and rough coarse aggregate, angular and rough coarse aggregate, rounded/spherical and smooth coarse aggregate, and flaky/elongated and rough coarse aggregate were prepared at 1:3:3 concrete mix ratio and 0.4 water cement ratio. Laboratory testing of specimens derived from the concrete specimens showed excellent results for cubical and rough coarse aggregate, irregular and rough coarse aggregate, and angular and rough coarse aggregate. Specimens from the rounded/spherical and smooth coarse aggregate, and flaky/elongated and rough coarse aggregate performed poorly in laboratory. The study therefore recommends the use of cubical and rough coarse aggregate, and irregular and rough coarse aggregate in the production of roller-compacted concrete for pavement construction and maintenance.